The influence of biochar and compost mixtures, water content, and gas flow rate, on the continuous adsorption of methane in a fixed bed column. (1st March 2019) - La, Helen; Hettiaratchi, J. Patrick A.; Achari, Gopal
Abstract: Biofiltration is an excellent alternative for the treatment of diffuse emissions of methane (CH4 ) that cannot be treated by physical/chemical means or recovered for energy. Despite the advances on CH4 biological treatment technologies, they are limited by the low aqueous solubility of CH4 into the biofilm where CH4 mineralization occurs. In this study, the CH4 adsorption kinetics, adsorption capacity and transport behavior of CH4 was studied in batch experiments and in a fixed-bed column by varying the biochar and compost mixtures under 5-levels, 3 different water contents (dry, 15% and 30% water holding capacity), and 2 inlet flow rates. Experimental results were formally tested using analysis of variance (ANOVA) in order to draw objective conclusions based on statistical inference. As CH4 biofiltration requires water addition to maintain microbial activity, these results indicate adsorption capacity is not lost with water addition if biochar content is the dominant packing material. The Langmuir isotherm described the data best (R 2  = 0.99). Maximum adsorption capacity by monolayer adsorption, or qmax, is relatively similar with or without the addition of water as long as the biochar component is the dominant material at 3.5 mg CH4 /g medium for a 7:1 biochar: compost, v/v mixture. Empirical regression models for qo, kTh, (Thomas model) and τ and KYN (Yoon-Nelson model) were developed for the break through curves of CH4 . The current work demonstrates the applicability of utilizing biochar, a relatively inexpensive adsorbent, can compensate for the low solubility of CH4 and overcome the rate-limiting step of mass transfer from the gas phase and into the methanotrophic biofilm. Further, biochar may be a reliable back-up system for CH4 storage especially for fluctuating inlet loads that may be encountered in industrial applications adsorbing up to 13 mg CH4 /g biochar under dry conditions. Graphical abstract: Image 1 Highlights: Methane adsorption on biochar/compost was assessed in batch and fixed-bed studies. Effect of compost, water, and CH4 flow rate were evaluated for adsorption capacity. Biochar was assessed as an adsorbent and for CH4 storage in biofiltration. Adsorption was explained by Langmuir kinetics. Breakthrough of CH4 were modeled using Bohart-Adams, Thomas, and Yoon-Nelson models.